Effect of oral contraceptive cycle phase on performance in team sport players - Rechichi, C.; Dawson, B. (Journal of Science and Medicine in Sport, 2009)
The purpose of this study was to examine whether common team sport performance variables (anaerobic power, reactive strength and repeat sprint ability) are affected by acute hormonal fluctuation within a monophasic oral contraceptive (OC) cycle. Ten female team sport athletes completed performance tests at three time points of a single OC cycle, during the consumption phase (CONS), early (WITH1) and late in the withdrawal phase (WITH2). Tests included drop jumps (30 cm and 45 cm heights), a counter movement jump, a 10 s cycle sprint test and a 5× 6 s repeated sprint cycle test. Resting endogenous serum oestradiol and progesterone concentrations were also measured. No significant differences were observed between phases for the counter movement jump and cycle tests (total work and peak power). Reactive strength measured from the 30 cm drop height was significantly lower during WITH2 (162 ± 38 cm s-1) compared to both CONS (177 ± 44 cm s-1) and WITH1 (178 ± 40 cm s-1) (p < 0.05). Reactive strength measured from the 45 cm drop height was significantly higher in CONS (178 ± 48 cm s-1) compared to both WITH1 and WITH2 (161 ± 39 cm s-1 and 158 ± 29 cm s-1, respectively) (p < 0.05). Serum oestradiol levels were greater during WITH2 compared to both WITH1 and CONS (p < 0.05) but there was no difference in serum progesterone levels. The results demonstrate that for female team sport athletes, only reactive strength varied significantly throughout an OC cycle, possibly due to the action of hormones on neuromuscular timing and the stretch-shortening cycle.